Economic and occupational integration of newcomers - Joel S. Fetzer (Luxembourg Income Study (LIS), 2010)
This paper summarizes the economic context of immigration in Luxembourg before examining the determinants of individual and cross-national unemployment, income, and occupational mobility. It finds that although being an immigrant in itself does not seem to cause substantial economic advantage or disadvantage, correlated factors such as education and the nationality of one's parents do. Cross-nationally, Luxembourg does not have an admirable record on unemployment or income for immigrants, but the foreign-born do seem to achieve relatively high levels of upward mobility. Pan-EU analysis suggests that the main source of such intergenerational mobility is Luxembourg's sustained economic growth.
Keywords: 330; Migranten; Intergenerationale Übertragung; Einkommen; Arbeitsmobilität; Wirtschaftswachstum; Luxemburg